(untitled) (Al-Academy, 2025)
Educational units are considered one of the forms of curriculum development to benefit the new information revolution. They are an organization planned in a way that includes the educational material, methods, accompanying educational activities and teaching methods, in addition to the evaluation process, which together leads to achieving the desired goals To go through the experiences that entail It requires the learner to acquire information, skills and attitudes. The researcher aimed to build an educational unit to develop female students’ skills in manufacturing graduation clothes and accessories using sustainable materials and measuring their effectiveness. The research followed the quasi-experimental approach, and the research sample consisted of (25) female students from the College of Design at Umm Al-Qura University, and the educational unit was implemented in the academic year (2022 AD).